Adsorption of hydrophobically modified polyacrylamide P(AM-NaAA-C16DMAAC) on model coal and clay surfaces and the effect on selective flocculation of fine coal. (October 2019) - Zou, Wenjie; Gong, Lu; Huang, Jun; Zhang, Zhijun; Sun, Chunbao; Zeng, Hongbo
Graphical abstract: Highlights: Hydrophobically modified polyacrylamide (HMPAM) facilitates selective flocculation. Pre-formed calgon layer inhibits the adsorption of HMPAM on silica and alumina. HMPAM shows significant adsorption on calgon-treated asphaltene surface. Selective flocculation flotation tests demonstrate excellent performance of HMPAM. Abstract: Selective flocculation separation has been widely used in fine coal flocculation. In order to promote the adsorption selectivity of flocculants onto coal surface, hydrophobically modified polyacrylamide P(AM-NaAA-C16 DMAAC) was synthesized. The adsorption of P(AM-NaAA-C16 DMAAC) on model clay and coal surfaces (i.e., silica, alumina and asphaltene surfaces) was investigated using quartz crystal microbalance with dissipation (QCM-D) monitoring technique. Floc size distribution, Fourier transform infrared spectrum, zeta potential measurement and selective flocculation flotation test were also conducted to study the performance of P(AM-NaAA-C16 DMAAC) in the separation of fine coal. QCM-D measurements showed that a thin and rigid adsorption layer was formed on silica and alumina surfaces after injecting 1 mM sodium hexapolyphosphate (Calgon). This pre-formed layer inhibited the further adsorption of P(AM-NaAA-C16 DMAAC) on silica and alumina. Meanwhile, the asphaltene surface could not be passivated by calgon due to the weak and reversible adsorption. Thus, a significant amount of P(AM-NaAA-C16 DMAAC) (20 mg/L) absorbed on the calgon-treated asphaltene surface in 100 mM KCl solution was detected. With 20 mg/L P(AM-NaAA-C16 DMAAC) in 100 mM KCl and 1 mM calgon solution, the maximum diameters of 10%, 50% and 90% of the cumulative volume distributions of the floc, i.e., d 10 (20.29 μm), d 50 (45.55 μm) and d 90 (89.99 μm) of the coal floc were 7.42, 3.20 and 2.19 times of those of kaolinite floc, respectively. Clean coal with a combustible recovery of 80.87% and ash content of 9.78% was obtained at a dosage of 5 g/t of P(AM-NaAA-C16 DMAAC) and 900 g/t kerosene. Experimental results demonstrated that selective flocculation flotation with P(AM-NaAA-C16 DMAAC) could enhance the recovery of fine coal particles with a lower dosage of collector. Our work sheds lights on the fundamental and practical understanding of the hydrophobic interactions in the selective flocculation of coal in the industries, and rational development of flocculants with better selectivity and flocculation efficiency.